Factors associated with hypertension in women of childbearing age - Kusumaningrum, Tiyas; Pratiwi, ka Nur; Nur Andini, Nike Wahyu; Armini, i Ketut Alit; Nursalam; Arief, Yuni Sufyanti (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate factors associated with hypertension in women of childbearing age. Method: The correlational, cross-sectional study was done in Madiun, East Java, Indonesia, in August 2021 after approval from the Faculty of Nursing, Universitas Airlangga, Surabaya, Indonesia. The sample comprised women of childbearing age who were married and not pregnant. Data was collected using questionnaires, while blood pressure, height and weight of the subjects were measured and noted. Data were analysed using Spearman Rho test. Results: Of the 311 subjects with mean age 32.06±7.10 years, 184(59.2%) were housewives; 153(49.2%) had studied up to the Senior High School level; 166(53.38%) were overweight; 157(50.48%) had family history of hypertension; 99 (31.83%) were exposed to cigarette 1-2 hours a day; 141(45.34%) were using hormonal contraception for >2 years; 94(30.23%) had low physical activity; 148 (47.59%) had high sodium consumption; and 139(44.69%) consumed coffee 2-3 cup/day. Hypertension prevalence was 123(39.55%). BMI (r=0.750), family history (r=0.763), exposure to cigarette smoke (r=0.755), physical activity level (r=-0.806), and sodium (r=0.505) were significantly associated with hypertension (p<0.05). Hormonal contraception (r=0.271) and coffee consumption (r= 0.127) had a weak association with hypertension incidence (p>0.05). Conclusion: Risk of hypertension in women increased for those with high body mass index, family history, high exposure to cigarette smoke, and high sodium intake. Keywords: Hypertension, cigarette smoke, hormonal contraception, obesity, sodium